Influence of Previous General Anesthesia on Cognitive Impairment: An Observational Study Among 151 Patients - Linassi, Federico; De Laurenzis, Alessandro; Maran, Eleonora; Gadaldi, Alessandra; Spano', Leonardo; Gerosa, Gino; Pittarello, Demetrio; Zanatta, Paolo; Carron, Michele (Frontiers in Human Neuroscience, 2022)
Introduction: Preoperative neurocognitive disorder (preO-NCD) is a common condition affecting 14%–51.7% of the elderly population. General anaesthesia has already been associated with one-year postoperative neurocognitive disorder (PostO-NCD), in particular a deficit in executive function, detected by the Trail Making Test B (TMT-B), but its long-term effects on cognitive function have not been investigated. We aim to detect preO-NCD prevalence in patients scheduled for cardiac surgery and further investigate the possible role of previous general anaesthesia (pGA) in general preoperative cognitive status (measured via Montreal Cognitive Assessment (MoCA)) and/or in executive functioning (measured via TMT-B). Methods: In this observational, prospective study, 151 adult patients scheduled for elective cardiac surgery underwent MoCA and TMT-B. Age, education, pGA, comorbidity, and laboratory data were collected. Results: We found a general cognitive function impairment of 79.5% and an executive function impairment of 22%. Aging is associated with the increased likelihood (OR 2.99, p = 0.047) and education with the reduced likelihood (OR 0.35, p = 0.0045) of general cognitive impairment, whereas only education was significantly associated with the reduced likelihood (OR 0.22, p = 0.021) of executive function impairment. While pGA did not significantly affect preO-NCD, a noteworthy interaction between aging and pGA was found, resulting in a synergistic effect increasing the likelihood of executive function impairment (OR 9.740, p = 0.0174). Conclusions: We found a high prevalence of preO-NCD in patients scheduled for cardiac surgery. Age increase is highly associated with general cognitive function impairment (not for pGA). However, older patients with at least one pGA appeared to have an increased risk of preO-NCD, especially executive function impairment, suggesting that in this population, TMT-B should be associated with MoCA in the preoperative cognitive evaluation.